English Teachers' Perceptions of the Guru Penggerak Program in Bengkulu Tengah - Dahlia; Wisma Yunita (JPG: Jurnal Pendidikan Guru, 2025)
The Guru Penggerak program aims to improve teacher competency and develop a competent environment dedicated to improving the quality of student learning processes and outcomes. The goal of this research to find out the English teachers’ perception of guru Penggerak program. This study focused on English teachers from Bengkulu Tengah who have participated in the Guru Penggerak Programs. This research used a mixed-methods approach, the research combines quantitative data gathered from structured questionnaires with qualitative insights obtained through semi-structured interviews. The research involved English teachers of Guru Penggerak program at Bengkulu Tengah. The data analyzed with using quantitative and qualitative approach. The result showed that the teachers generally hold a positive view of the Guru Penggerak Program toward teachers’ competencies. The teachers’ perception of the program was largely positive, with most teachers reporting an increase in pedagogical, personal, professional, and social competencies The findings from this research can help inform policymakers and educational leaders about the program's strengths and areas needing enhancement, ultimately contributing to better educational practices in Indonesia.